2021
DOI: 10.1158/0008-5472.can-20-4192
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3σFunctions as an Intestinal Tumor Suppressor

Abstract: Although the 14-3-3σ gene was initially identified as a p53 target gene in colorectal cancer cells, its potential role in intestinal tumorigenesis has remained unknown. Here we determined that 14-3-3σ expression is significantly downregulated in primary human colorectal cancer when compared with adjacent normal colonic tissue in patient samples. Downregulation of 14-3-3σ in primary colorectal cancers was significantly associated with p53 mutation, increasing tumor stage, distant metastasis, and poor patient su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…It is well known that 14-3-3σ, one member of the 14-3-3 protein family, is crucial for nuclear signals by changing the subcellular localization of many of its binding partners, regulating signal transduction, apoptosis, checkpoint control, and nutrient sensing [29][30][31] . By phosphorylating amino acid motifs, 14-3-3 protein can also act as a lipid raft protein, targeting intracellular proteins and stimulating their translocation [32][33][34] .…”
Section: Lplunc1 Enhances the Nuclear Translocation Of Phb1 In Npc Cellsmentioning
confidence: 99%
“…It is well known that 14-3-3σ, one member of the 14-3-3 protein family, is crucial for nuclear signals by changing the subcellular localization of many of its binding partners, regulating signal transduction, apoptosis, checkpoint control, and nutrient sensing [29][30][31] . By phosphorylating amino acid motifs, 14-3-3 protein can also act as a lipid raft protein, targeting intracellular proteins and stimulating their translocation [32][33][34] .…”
Section: Lplunc1 Enhances the Nuclear Translocation Of Phb1 In Npc Cellsmentioning
confidence: 99%
“…For the generation of STAT3 and c-JUN expression signatures, we compiled RNA-Seq datasets from the NCBI Gene Expression Omnibus (GEO), as described recently 43 . Differentially regulated genes were identified using RNA-Seq data from cell lines/tissues with STAT3, c-JUN, or SRF ectopic expression or knockdown (KD)/knockout (KO).…”
Section: Methodsmentioning
confidence: 99%
“…Differential expression between tumors of different stages was calculated using one-way ANOVA with a post-test for linear trend from stage 1 to stage 4. Gene Set Enrichment Analysis (GSEA) of curated gene sets obtained from the Molecular Signatures database (MSigDB) 35 , or as indicated 43 , 49 , was performed on pre-ranked gene lists ordered by expression correlation coefficients (Pearson) with the Δ34a expression signature, mature miR-34a, or CSF1R expression, as described previously 21 . The significance of enrichments is presented by normalized enrichment scores (NES) and false discovery rate-adjusted q values.…”
Section: Methodsmentioning
confidence: 99%
“…14-3-3 σ, as a member of the highly conservative 14-3-3 protein family, mainly exists in epithelial cells and can promote G2-phase block of the cell cycle after DNA damage by interacting with a variety of signal proteins such as CDK2, CDC2, etc., and regulate cell growth, differentiation and proliferation in mammal cells [ 14 , 15 , 16 ]. It also acts as a key regulator of p53 to control mitotic progression in response to DNA damage and inhibits the development of several substantial tumors, such as nasopharyngeal, colorectal and breast cancers [ 17 , 18 , 19 , 20 , 21 ]. In some studies on lung and gastric cancers, 14-3-3σ was found to show high expression in cancer tissues, promoting the progression of tumorigenesis [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%